Metabolic equivalent of task scores avoid the ceiling effect observed with conventional patient-reported outcome scores following knee arthroplasty. (6th March 2023) - Patel, Arjun; Edwards, Thomas C.; Jones, Gareth; Liddle, Alexander D.; Cobb, Justin; Garner, Amy
Abstract : Aims: The metabolic equivalent of task (MET) score examines patient performance in relation to energy expenditure before and after knee arthroplasty. This study assesses its use in a knee arthroplasty population in comparison with the widely used Oxford Knee Score (OKS) and EuroQol five-dimension index (EQ-5D), which are reported to be limited by ceiling effects. Methods: A total of 116 patients with OKS, EQ-5D, and MET scores before, and at least six months following, unilateral primary knee arthroplasty were identified from a database. Procedures were performed by a single surgeon between 2014 and 2019 consecutively. Scores were analyzed for normality, skewness, kurtosis, and the presence of ceiling/floor effects. Concurrent validity between the MET score, OKS, and EQ-5D was assessed using Spearman's rank. Results: Postoperatively the OKS and EQ-5D demonstrated negative skews in distribution, with high kurtosis at six months and one year. The OKS demonstrated a ceiling effect at one year (15.7%) postoperatively. The EQ-5D demonstrated a ceiling effect at six months (30.2%) and one year (39.8%) postoperatively. The MET score did not demonstrate a skewed distribution or ceiling effect either at six months or one year postoperatively. Weak-moderate correlations were noted between the MET score and conventional scores at six months and one year postoperatively. Conclusion: In contrast to the OKS and EQ-5D, the MET score was normally distributed postoperatively with no ceiling effect. It is worth consideration as an arthroplasty outcome measure, particularly for patients with high expectations. Cite this article: Bone Jt Open 2023;4(3):129–137.